Rural homesteads offers for tourists in the Chernivtsi region - Скутар, Тетяна; Кілінська, Клавдія (My University, 2014)
Rural tourism is a priority trend in social-economic development of rural areas in the Chernivtsi region. There has been an increase in the number of rural homesteads in the region in recent years. The improvement of infrastructure and rural tourism services promotion are the important problems for rural tourism in the region. The article deals with the types of tourism services, which are proposed by homesteads in the Chernivtsi region, and the information and advertising sources, which are used for agritourism product promotion.
Keywords: rural tourism; rural homesteads offers; promotion of rural tourism; informational and promotional materials; informational promotional sources